Treatment of maxillary osteomyelitis after facial trauma - Mendonça, José Carlos Garcia de; Arashiro, Fabio Nakao; Aguillera, Maísa de Oliveira; Santos, Muryllo Eduardo Sales dos; Pelissaro, Gustavo Silva; Gaetti Jardim, Ellen Cristina (ARCHIVES OF HEALTH INVESTIGATION, 2021)
Osteomyelitis is an inflammatory condition in the medullary spaces or the cortical surface of bones. It can be acute or chronic and extend beyond the original site. Also, it can be caused by several factors, among them as a result of untreated dental trauma. Correct diagnosis and individualized treatment are essential for success. The aim is to report a case of chronic osteomyelitis due to a history of dental trauma in the anterior region of the maxilla in a 21-years-old patient without associated comorbidities, focusing on the success of the therapy employed. It is known that the treatment of osteomyelitis is still a challenge because of the microbiota present. The treatment recommended with higher success rates is the removal of bone sequestration associated with antibiotic therapy, which has shown satisfactory results and maintenance of the dental elements in function.